PEMANFAATAN DAUN MANGGA ARUM MANIS (Mangifera indica L.) SEBAGAI MINUMAN TEH CELUP [THE UTILIZATION OF ARUM MANIS MANGO LEAVES (Mangifera indica L.) AS TEA BAG DRINK] - Melanie Cornelia; Joshua Agus Sutisna (FaST : Jurnal Sains dan Teknologi, 2019)
Mango arum manis leaves (Mangifera indica L.) are leaves that contain antioxidants such as phenolics and flavonoids, and are beneficial for body health because they act as a deterrent to oxidative damage that can cause cancer. The purpose of this research was to utilize arum manis mango leaves as tea bag drinks with various drying methods (cabinet and sun). Next step is the process of making types of green tea and black tea. Selected dried tea was obtained from mango leaves with a cabinet drying method and the result was a type of green tea. From the data analysis conducted, this green tea has an IC value of 50 314.47 ± 11.58 ppm,  total phenolic of 1446.22 ± 58.12 mg GAE /L, total flavonoids of 1191.92 ± 17.00 mg QE /L , and total tannins 892.92 ± 23.92 mg TAE /L. The dried green tea samples obtained, weighed 1.5 g, 2.0 g, and 2.5 g were included in a tea bag and brewed with 1 minute, 3 minutes, and 5 minutes brewing by immersion and then the results of the tea bag drink. Those mango leaf tea bag drinks were analyzed for its antioxidant activity content and panelist acceptance. The weight of dried mango leaf tea (g) which was used to make tea bags and the duration of brewing had an effect on the antioxidant activity of mango leaf tea bags. The best choice weight and duration of brewing is mango leaf tea with 2.5 g of dried mango leaf weight with 5 minutes long brewing because it has antioxidant activity which is still good and favored by panelists. ABSTRAKDaun mangga arum manis (Mangifera indica L.) adalah daun yang memiliki kandungan antioksidan seperti fenolik dan flavonoid, dan bermanfaat untuk kesehatan tubuh karena berperan sebagai pencegah kerusakan oksidatif yang dapat menyebabkan kanker. Tujuan penelitian ini adalah memanfaatkan daun mangga arum manis sebagai minuman teh celup dengan variasi metode pengeringan (kabinet dan matahari). Selanjutnya dilakukan proses pembuatan jenis teh kering teh hijau dan teh kering teh hitam. Teh kering terpilih dari variasi metode pengeringan diperoleh dari daun mangga dengan metode pengeringan kabinet dan hasilnya jenis teh hijau. Dari data analisis yang dilakukan, teh hijau ini memiliki nilai IC50 314,47 ± 11,58 ppm, total fenolik 1446,22 ± 58,12 mg GAE/L, total flavonoid 1191,92 ± 17,00 mg QE/L, dan total tanin 892,92 ± 23,92 mg TAE/L. Sampel teh hijau kering yang diperoleh, ditimbang 1,5 g, 2,0 g, dan 2,5 g dimasukan dalam kantong teh dan  diseduh dengan lama penyeduhan 1 menit, 3 menit, dan 5 menit dengan cara pencelupan dan selanjutnya hasil minuman teh celup daun mangga tersebut dianalisis kandungan aktivitas antioksidan nya dan penerimaan panelis. Berat teh kering daun mangga (g) yang dipakai untuk dibuat teh celup dan lamanya penyeduhan, berpengaruh terhadap aktivitas antioksidan dari teh celup daun mangga. Berat dan lama penyeduhan terbaik adalah teh celup daun mangga dengan berat daun mangga kering 2,5 g dengan lama 5 menit penyeduhan karena memiliki aktivitas antioksidan yang masih baik dan disukai panelis.